The Framework of the system for the development of web app survey, i-LULACAST - Ibrahim, Illyani; Hj. Mohd. Noor, Norzailawati; Abdullah, Alias; Zakariya, Khalilah; Nizarudin, Norhanis Diyana; N Murtaza, Fatin Farhana (2021)
Protection on the framework of the system for the development of wen app survey namely IIUM Land Use and Landscape Character SurveyTool (i-LULACAST) that are designated for the purpose of data collection and analysis for Kajian Meningkatkan Imej Serta Identiti Bandar Diraja Pekan, Pahang.The framework of the system focussing on the functions and steps for adding users and selecting the data needed to be filled by users or experts in relation to the analysis for the Sultanate Land, Pekan